Analisa Optimalisasi Keuntungan dengan Integer Linear Programming dan Metode Branch and Bound pada Toko Bunga QuinnaStory - Ayunda Zuserain; Winarno Winarno; Billy Nugraha; Ade Momon (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
QuinnaStory Flower Shop produces flower buckets with 2 types of sizes, namely small flower buckets and large flower buckets. With current problems in the form of limited resources, lack of automatic cutting machines, manpower and optimization of production planning. This study aims to determine how to solve the search for maximum profit from production. The optimal solution based on the problem at QuinnaStory Flower Shop can be solved by integer linear programming approach. The method used in this research is the simplex method to look for maximum benefits. The results obtained required the production of 36 small flower buckets and 31.5 large flower buckets to obtain a maximum profit of Rp. 2,790,000, - However, the results of product production / day are still in decimal form. Therefore, it is continued with the branch and bound method to find non-decimal results. The result of the settlement is required to produce 36 small flower buckets and 31 large flower buckets / day to get a maximum profit of IDR 2,764,000.